Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Pemerintah Terhadap Kualitas Laporan Keuangan Daerah Pesawaran - Novriansyah, Erwin; Nilwan, Afrizal (Jurnal EMT KITA, 2024)
Pesawaran Regency is one of the regions in Lampung that has received the Fair Without Exceptions (WTP) predicate from the Financial Audit Agency (BPK). This research aims to measure the impact of existing variables on the quality of regional financial reports. This research uses a quantitative approach with a purposive sampling method and a Likert scale measurement. Data was collected by distributing questionnaires to 30 respondents, employees of the Regional Financial and Asset Management Agency (BPKAD) of Pesawaran Regency who focus on the financial sector. The research results show that variable X1, namely the accounting information system, and variable X2, namely the internal control system, influence the quality of financial reports. These findings contribute to further understanding regarding the role of accounting information systems and internal control in ensuring the quality of regional financial reports.